The steroidal lactone withaferin A impedes T-cell motility by inhibiting the kinase ZAP70 and subsequent kinome signaling - Mobashar Hussain Urf Turabe Fazil (2022)
The steroidal lactone withaferin A (WFA) is a dietary phytochemical, derived from Withania somnifera. It exhibits a wide range of biological properties, including immunomodulatory, anti-inflammatory, antistress, and anticancer activities. Here we investigated the effect of WFA on T-cell motility, which is crucial for adaptive immune responses as well as autoimmune reactions. We found that WFA dose-dependently (within the concentration range of 0.3-1.25 μM) inhibited the ability of human T-cells to migrate via cross-linking of the lymphocyte function-associated antigen-1 (LFA-1) integrin with its ligand, intercellular adhesion molecule 1 (ICAM-1). Coimmunoprecipitation of WFA interacting proteins and subsequent tandem mass spectrometry identified a WFA-interactome consisting of 273 proteins in motile T-cells. In particular, our data revealed significant enrichment of the zeta-chain-associated protein kinase 70 (ZAP70) and cytoskeletal actin protein interaction networks upon stimulation. Phospho-peptide mapping and kinome analysis substantiated kinase signaling downstream of ZAP70 as a key WFA target, which was further confirmed by bait-pulldown and Western immunoblotting assays. The WFA-ZAP70 interaction was disrupted by a disulfide reducing agent dithiothreitol, suggesting an involvement of cysteine covalent binding interface. In silico docking predicted WFA binding to ZAP70 at cystine 560 and 564 residues. These findings provide a mechanistic insight whereby WFA binds to and inhibits the ZAP70 kinase and impedes T-cell motility. We therefore conclude that WFA may be exploited to pharmacologically control host immune responses and potentially prevent autoimmune-mediated pathologies.